Differences in The Influence of Music Rhythm on Mood and Average Speed When Exercise - Hidayat, Alfian; Ananda Perwira Bakti; Noortje Anita Kumaat; Anindya Mar'atus Sholikhah (Universitas PGRI Palembang, 2024)
Running while listening to music is thought to be able to increase a person's average speed when running through the mood when listening to music. The aim of this research is to determine the difference between different musical rhythms on mood and average speed when running. The method in this research uses a pre-test and post-test to determine the mood of the sample being tested when running while listening to different music rhythms, while the post-test test is to determine the difference in the average speed of the sample when the test was carried out. The sample used in this research was class X high school students with an average age of 16 years. The measuring tools used in this research are the profile of mood states questionnaire to determine the difference in mood before and after treatment, and the Strava application to determine the difference in average sample speed when the test was carried out. The results of this study show that slow rhythmic music has more influence on a person's mood when running than moderate and fast rhythmic music. This is proven by the results of the questionnaire after the test was carried out that slow music has an average of 168, greater than moderate music with an average of 154 and fast music with an average of 34. Meanwhile, in terms of speed average, each different musical rhythm has difference to a person's average running speed. This is proven by the average test results (pace) with the Strava application, slow music has an average of 11 km/m, medium music 10 km/m and fast music 8 km/m. The conclusion obtained from this research is that slow music rhythms have more influence than medium and fast music rhythms on mood when running and different music rhythms make a person's average speed different when running depending on the rhythm of the music they listen to.